Il rilievo con drone nei centri storici - Zaira Baglione (GEOmedia, 2016)
The survey with an UAV in the city centre for a research project of the University of L'Aquila has been started the use of UAV technology in some areas damaged by the earthquake of 2009. A synergistic survey to highlight the criticality and monitor the state of the buildings in order to prevent the emergencies and innovate the remote sensing methodologies. The testimony of the project coordinator, Prof. Donatella Dominici, describing the results of the survey carried out with the multicopter.